2018
DOI: 10.1002/ejoc.201800499
|View full text |Cite
|
Sign up to set email alerts
|

Selective Formation of Monoacylated Diols through a Mild Passerini Reaction

Abstract: The synthesis of both regioisomers of monoacylated diols has been achieved in one simple step using a Passerini reaction. We examined various substrates and reaction conditions, and the results show that the regioselectivity of the reaction is governed by a choice between five‐ and six‐membered‐ring transition states, and by different rates of acyl migration under different reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Wang and co-workers examined the use of glycoaldehyde derivatives in the Passerini reaction and found that two different regioisomeric monoacylated diols could be attained depending on reaction conditions (Scheme ). The authors suspected that the two different products could arise from divergence in the reaction pathway after formation of the O-acyl imidate. Acyl transfer to the secondary hydroxyl group through a five-membered transition state would provide the monoacylated diol with a free primary hydroxyl group.…”
Section: Condensationsmentioning
confidence: 99%
“…Wang and co-workers examined the use of glycoaldehyde derivatives in the Passerini reaction and found that two different regioisomeric monoacylated diols could be attained depending on reaction conditions (Scheme ). The authors suspected that the two different products could arise from divergence in the reaction pathway after formation of the O-acyl imidate. Acyl transfer to the secondary hydroxyl group through a five-membered transition state would provide the monoacylated diol with a free primary hydroxyl group.…”
Section: Condensationsmentioning
confidence: 99%
“…To evaluate the most appropriate reaction conditions for the synthesis of α-acyloxy ketones, an initial search for the best solvent was carried out in a batch microwave (MW) preliminary optimization using solvents typically applied in Passerini reactions (Wu et al, 2018) (Table 1) and considering our previous experience in MW-mediated MCR reactions (Barreto et al, 2011a,b, 2014; Salvador et al, 2015; Barreto and Andrade, 2018, 2019). Formation of the Passerini product in toluene at 110°C was not observed probably be due to the low microwave dielectric heating property of this solvent (Gabriel et al, 1998; Kappe et al, 2012) (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…The Passerini three-component reaction (P-3CR) 13 was developed aer Passerini's discovery of the reaction between isocyanides, aldehydes, and carboxylic acids to produce a-acyloxy carboxamides in 1921. 14,15 It has since grown to be a potent tool in combinatorial chemistry and hetero cyclic chemistry for drug discovery as well as natural product synthesis. [16][17][18] Passerini reaction has been known for over 80 years, little is known about the scope of carbonyl-type electrophiles that undergo the reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%